Kajian Macam Bokashi Terhadap Pertumbuhan dan Hasil 2 Varietas Okra (Abelmoschus esculentus L. Moench) - Fransiska Mardiyana; Siswadi Siswadi; Saiful Bahri (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2022)
Using green okra and red okra plant kinds, the researchers want to assess the growth response and yield of the plants after they have been fertilized with bokashi fertilizer, which is made by the use of tea dregs and water hyacinth. During the period September to November 2021, this study was carried out Harjosari Village is located in the Bawen District of the Semarang Regency. The study used a Split Plot Completely Randomized Design (RAKL) with two treatment components, and the findings were reported in Psychological Science.., namely okra varieties and bokashi fertilizer. The number of treatments was 8 and repeated 4 times. V1B0 ; Varieties of green okra without bokashi fertilizer (0 kg), V1B1 ; Varieties of green okra with bokashi fertilizer tea dregs (1 kg), V1B2 ; Green okra variety with water hyacinth bokashi fertilizer (1 kg), V1B3 ; Green okra variety with bokashi fertilizer mixed with tea dregs and water hyacinth (1 kg), V2B0 ; Varieties of red okra without bokashi fertilizer (0 kg), V2B1; Red okra variety with tea dregs bokashi fertilizer (1 kg), V2B2 ; Red okra variety with water hyacinth bokashi fertilizer (1 kg), V2B3 ; Red okra variety with bokashi fertilizer mixed with tea dregs and water hyacinth (1 kg). Furthermore, the measured parameters will be analyzed using Anova and further tested using the 5% BNT test. The study found that applying up to 1 kg of bokashi fertilizer containing tea dregs and water hyacinth had a highly significant influence on plant height growth and fruit yield.